2007
DOI: 10.4028/www.scientific.net/msf.539-543.3781
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Post-Weld Heat Treatments to Restore the Corrosion Resistance of Friction Stir Welded Aluminum Alloy 7075-T73 vs. 7075-T6

Abstract: Friction stir welding (FSW) is rapidly becoming accepted as a viable manufacturing process for aerospace applications. One potential area of concern, however, is the corrosion resistance of some FSW joints. While the corrosion resistance of friction stir welded 7075 aluminum has been investigated, and attempts made to enhance its corrosion resistance through different combinations of starting temper and post-weld artificial aging (PWAA) treatments, a clear approach for selecting pre-temper conditions and PWAA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Alloy 7075 was found to be less sensitive to SCC (73% of strain to failure in air), with a T73 post-weld temper restoring this to 85%. Widener et al 420 found joining 7075 material originally in the T73 condition followed by PWAA to be preferable (in terms of higher tensile and yield strengths and better exfoliation corrosion resistance) to welding in the T6 temper condition followed by aging to T73. Retrogression and re-aging treatments were not found to improve joint properties of T6 material due to the severity of the overaging in the HAZ caused by the welding process.…”
Section: Strategies To Reduce Corrosion Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Alloy 7075 was found to be less sensitive to SCC (73% of strain to failure in air), with a T73 post-weld temper restoring this to 85%. Widener et al 420 found joining 7075 material originally in the T73 condition followed by PWAA to be preferable (in terms of higher tensile and yield strengths and better exfoliation corrosion resistance) to welding in the T6 temper condition followed by aging to T73. Retrogression and re-aging treatments were not found to improve joint properties of T6 material due to the severity of the overaging in the HAZ caused by the welding process.…”
Section: Strategies To Reduce Corrosion Susceptibilitymentioning
confidence: 99%
“…Overall, 4 h at 190uC was found both to stabilise the microstructure and to enhance the corrosion resistance for 7075, with only a slight reduction in tensile strength and the added advantage of annealing out residual stresses. 420 Less precise treatments have been applied using local heating of joints with torch flames in 7075 and 2219. 414 The effect of starting temper of the parent material and PWHTs were investigated for FSW joints in 2024.…”
Section: Strategies To Reduce Corrosion Susceptibilitymentioning
confidence: 99%
“…It has also been shown that micro arc oxidation/ coatings improves the corrosion resistance of friction stir welded Al alloys [23,24]. Beneficial heat treatments have also been reported for dissimilar weld of AA7075 and AA2024 [25,26].…”
Section: /3mentioning
confidence: 99%
“…4 These galvanic cells can lead to undesirable corrosion failures in service. In a bid to reduce corrosion susceptibilities in friction stir welds, post weld heattreatment/artificial aging, 3,[5][6][7] laser surface melting, [8][9][10][11][12] cold sprayed aluminum 13 and micro-arc oxidation coating 14 have been employed in recent times. Whilst post weld heat-treatment has been reported to improve the corrosion resistance of certain friction stir welded aluminum alloys 3,7 and to improve the mechanical properties of the low-strength weld regions , 15 its suitability for in-service applications is in doubt because of the timing involved and the large structure sizes employed commercially.…”
mentioning
confidence: 99%